2016
DOI: 10.1002/mnfr.201500667
|View full text |Cite
|
Sign up to set email alerts
|

L‐cysteine supplementation upregulates glutathione (GSH) and vitamin D binding protein (VDBP) in hepatocytes cultured in high glucose and in vivo in liver, and increases blood levels of GSH, VDBP, and 25‐hydroxy‐vitamin D in Zucker diabetic fatty rats

Abstract: ScopeVitamin D binding protein (VDBP) status has an effect on and can potentially improve the status of 25(OH) vitamin D and increase the metabolic actions of 25(OH) vitamin D under physiological and pathological conditions. Diabetes is associated with lower levels of glutathione (GSH) and 25(OH) vitamin D. This study examined the hypothesis that upregulation of GSH will also upregulate blood levels of VDBP and 25(OH) vitamin D in type 2 diabetic rats.Methods and resultsL‐cysteine (LC) supplementation was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 47 publications
0
41
0
2
Order By: Relevance
“…Logistic regression in our study revealed positive correlation among plasma VDBP, 25(OH)D, and GSH levels. Consistently, it has been pointed out that positive link between plasma levels of VDBP and 25(OH)D and those of GSH; specifically, lower plasma levels of VDBP and 25(OH)D correlated with lower GSH level, and increases in GSH level upregulated 25(OH)D and VDBP status in Zucker diabetic fatty rats . Supplementation of GSH could raise blood levels of VDBP and vitamin in African‐American patients with type 2 diabetes .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Logistic regression in our study revealed positive correlation among plasma VDBP, 25(OH)D, and GSH levels. Consistently, it has been pointed out that positive link between plasma levels of VDBP and 25(OH)D and those of GSH; specifically, lower plasma levels of VDBP and 25(OH)D correlated with lower GSH level, and increases in GSH level upregulated 25(OH)D and VDBP status in Zucker diabetic fatty rats . Supplementation of GSH could raise blood levels of VDBP and vitamin in African‐American patients with type 2 diabetes .…”
Section: Discussionmentioning
confidence: 75%
“…Consistently, it has been pointed out that positive link between plasma levels of VDBP and 25(OH)D and those of GSH; specifically, lower plasma levels of VDBP and 25(OH)D correlated with lower GSH level, and increases in GSH level upregulated 25(OH)D and VDBP status in Zucker diabetic fatty rats. 10 Supplementation of GSH could raise blood levels of VDBP and vitamin in African-American patients with type 2 diabetes. 12 Another study also suggested a significant positive correlation between GSH level and blood levels of L-cysteine (LC) and vitamin D in type 2 diabetic patients.…”
Section: Postoperative Plasma Vdbp 25(oh)d and Gsh Levels Are Incmentioning
confidence: 99%
See 2 more Smart Citations
“…Взаимодействие комплекса рецептора VDR и 1,25D с ядерным рецептором цисретиноевой кислоты и образование гетеродимера объясняет эффект на гены-мишени, участвующие в регуляции роста и дифференцировке клеток [1,2]. Важным эффектом витамина А является протекция токсичности витамина D за счет снижения экспрессии витамин-К-зависимых белков [1][2][3]. Эти и другие многочисленные данные положены в основу концепции «витамин D + 12 витаминов», предложенной В.Б.…”
Section: лукиенко еп максимчик юз романчук юг радута еф мunclassified